Association between Dietary Patterns and Handgrip Strength: Analysis of the Korean National Health and Nutrition Examination Survey Data Between 2014 and 2017 - Kang, Yunkoo (Nutrients, 2020)
Non-invasive anthropometric measurement methods such as those for measuring height and weight are crucial in pediatric patients. However, research focusing on the association between the type of dietary pattern and handgrip strength and handgrip-to-weight ratio in adolescents has not been carried out yet. This cross-sectional analysis of the 2014–2017 Korean National Health and Nutrition Examination Survey assessed 2327 adolescents (aged 10–18 years) who had their handgrip strength measured and analyzed its association with dietary pattern. The clusters were examined for nutritional values, and the ready-to-eat, balanced, and Western-style fast-food clusters were ultimately generated. Overall, 85.6% of the participants were assigned to a ready-to-eat dietary pattern, 9.3% to a Western-style fast-food dietary pattern, and 5.1% to a balanced dietary pattern. Compared with the participants following a balanced dietary pattern, those following a ready-to-eat dietary pattern were shown to have a significantly lower handgrip strength and handgrip-to-weight ratio. Decreased handgrip strength and handgrip-to-weight ratio values in participants following ready-to-eat dietary patterns indicate a diffuse problem in adolescents’ health and possibly imply an association between reduced muscle quality and dietary pattern. Therefore, the overall environmental factors potentially inducing such unhealthy dietary preferences should be investigated, and appropriate lifestyle changes in Korean adolescents should be encouraged.